The real ACT prep guide - ACT (2005)
The only official prep guide from the makers of the ACT;Includes 3 real ACT tests."--Cover, 1st ed.; "The only guide to include 3 real ACT tests."--Cover, 2nd ed.; "The only guide to include 5 real ACT tests."--Cover, 3rd ed.